Trichomonas Vaginalis: Its Morphology, Taxonomy and Transmission Mode: A Descriptive Review - Al-Ataby, Fatimah. H.; Radhi, Lamyaa. Y. (Journal of Science in Medicine and Life, 2025)
Trichomonas vaginalis is a protozoan parasite and a sexually transmitted disease (STD) of global significance, responsible for trichomonosis. This parasite can infect the urogenital tract of both females and males globally. T. vaginalis is a flagellated, anaerobic protozoan parasite. The primary objective of the present investigation is to acquire a sufficient amount of information regarding Trichomonas vaginalis, including transmission, taxonomy, morphology, and diagnosis.